O Programa de Estudantes-Convênio de Graduação: (re)construção de identidades étnico-raciais no âmbito das políticas públicas de internacionalização da educação superior no Instituto Federal do Ceará - Pedrosa, Ricardo da Silva (2018)
The Undergraduate Student Agreement Program (Programa de Estudantes-Convênio de Graduação - PEC-G) provides training for students from countries of the African continent in Brazilian higher education institutions. These exchange students have their coming and academic course subsidized by the public policies of internationalization of higher education. However, their permanence and development as immigrant citizens be permeated with the dynamics of ethnic-racial relations and tensions in the social environment of the city and the host institution (PEDROSA, 2016). Thus, I start from the following question: in what meaning can the PEC-G be evaluated from the experiences of the (re) construction of Afrodescendant ethnic-racial identities of the students of the program? The objective of this study is to highlight the experiences of (re) construction of Afro-descendant ethnic-racial identities as an in-depth evaluation dimension of the PEC-G academic mobility program. The evaluative proposal of the research, characterized as an in-depth assessment of the PEC-G,having as a locus a higher education institution located in Fortaleza (BR), namely the Federal Institute of Education of Ceará (IFCE). Using an interdisciplinary perspective, I approach the question of identities as a process constituted from the interactions with the other and with the socially generated images in the culture (HALL 2003, 2009, 2011). The ethno-cultural dimension of identities will be focused, emphasizing the material production of artifacts, knowledges and sentiments that carry out the process of identification / differentiation of the subject with an ethnic-racial matrix (FANON, 2008; GILROY, 2002). Considering that the identity processes under study are not far from their historical place of manifestation, I try to present a dynamic of identity in the context of the African diaspora in Ceará (LANGA, 2016). The methodological perspective adopted was qualitative of ethnographic inspiration and focused on the question of the identity of a global southern point (SANTOS, B. S., 2006,2007). In the exploratory phase, reports were collected on the coexistence of the IFCE servers with the PEC-G students. The fieldwork was started with observations of the daily life of GPEC students, especially at the planning and execution times of the African Cultural Weeks of 2014 and 2015, with re-elaboration of materials collected from 2013 to the present moment (printed news and on the institution's website, memos collected in sectors of the IFCE and photographic records). I assumed as the main investigative strategy the recording of the experience reports of nine PEC-G / IFCE students. As a technique for analyzing information collected on the identity processes of these students, I take as basis the Content Analysis (BARDIN, 2009) and the Bakhtin Discourse Analysis (BAKHTIN, 2006; MUSSALIM, 2001;VYGOTSKI, 2001). Ethnic-racial experience makes complex the reality experienced by PECG students. Between the arrival, the arrival, the obtaining of a diploma and the return to their countries of origin, the identities of these students be demoted and it moves other identities with which it begins to interact. In the interstices between the subjects, manifestation of their ethnic groups and the confluence between public policies of internationalization of higher education and the cultural and affirmative policies of the African ethnic matrix is that the program is done.